How big of an effect do small dams have?: using ecology and geomorphology to quantify impacts of low-head dams on fish biodiversity - Fencl, Jane S. (Kansas State University, 2015)
In contrast to well documented adverse impacts of large dams, little is known about how smaller low-head dams affect fish biodiversity. Over 2,000,000 low-head dams fragment United States streams and rivers and can alter biodiversity. The spatial impacts of low-head dams on geomorphology and ecology are largely untested despite how numerous they are. A select review of how intact low-head dams affect fish species identified four methodological inconsistencies that impede our ability to generalize about the ecological impacts of low-head dams on fish biodiversity. We tested the effect of low-head dams on fish biodiversity (1) upstream vs. downstream at dams and (2) downstream of dammed vs. undammed sites. Fish assemblages for both approaches were evaluated using three summary metrics and habitat guilds based on species occurrence in pools, riffles, and runs. Downstream of dams vs. undammed sites, we tested if (a) spatial extent of dam disturbance, (b) reference site choice, and (c) site variability altered fish biodiversity at dams. Based on information from geomorphic literature, we quantified the spatial extent of low-head dam impacts using width, depth, and substrate. Sites up- and downstream of dams had different fish assemblages regardless of the measure of fish biodiversity. Richness, abundance and Shannon’s index were significantly lower upstream compared to downstream of dams. In addition, only three of seven habitat guilds were present upstream of dams. Methodological decisions about spatial extent, and reference choice affected observed fish assemblage responses between dammed and undammed sites. For example, species richness was significantly different when comparing transects within the spatial extent of dam impact but not when transects outside the dam footprint were included. Site variability did not significantly influence fish response. These small but ubiquitous disturbances may have large ecological impacts because of their potential cumulative effects. Therefore, low-head dams need to be examined using a contextual riverscape approach. How low-head dam studies are designed has important ecological insights for scientific generalizations and methodological consequences for interpretations about low-head dam effects. My research provides a template on which to build this approach that will benefit both ecology and conservation.
Keywords: Low-head dam; Fish; Community; Assemblage; Fluvial geomorphology; River; Biology (0306); Ecology (0329); Environmental Sciences (0768)